Densidade mineral óssea em adolescentes praticantes e não praticantes de atividade esportiva - Caputo, Eduardo Lucia (2012)
The potentiation of bone mass peak by physical exercise during adolescence can reduce the risk of osteoporosis in adulthood, especially in women. The aim of this study was to verify the differences in bone mineral density (BMD) of adolescent females, aged between 13 and 17 years, involved in extracurricular sports activities for a period of six months, three times a week (n = 27) and girls who had only the physical education classes (n = 25). In addition association between BMD and body composition and physical fitness components in these individuals was analysed. BMD was measured by Dual Emission X-ray absorptiometry (DXA). Tests of speed, long jump and agility were performed. The sports group showed increased values of the density of left and right arms and legs, total body, trochanteric region, lumbar spine and total body without a head. In the control group the variables weight, body fat percentage and horizontal jump presented itself as predictors of BMD in the left and right leg. In the group of sports density of lumbar spine shown to be predicted by height, age and speed. In right and left legs variables weight, age and lean mass proved to be good predictors of BMD. Participation in sports activities, with a weekly frequency of three times, may confer benefits on bone density in adolescent girls aged between 13 and 17 years.